Intellectual Capital Terhadap Nilai Pasar Dan Kinerja Keuangan Perusahaan Dengan Value Added Intellectual Capital (Studi Pada Perusahaan Manufaktur di Bursa Efek Indonesia Tahun 2008-2011) - Sofie Sofie; Ari Prihartini; Rinda Liana (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2012)
This study aims to ident6 and analyze the effect of intellectual capital as one of the company's intangible assets to market value and financial performance.of the company-manufacturing companies using the Value Added Intellectual Capital (VAIC m). The analysis method used is multiple panels because the structure of the data used in this research is the data panel. The results of the hypothesis theory shows that the intellectual capital has significant effect on the market value and performance of the company. The three components of intellectual capital, as the physical capital efficiency, human capital and structural capital efficiency, have a positive effect on firm value and performance of companies that dproksi by ROA, ATO, ROE and OI / S. So do the results of statistical tests, except for the efficiency of the human capital and structural capital efficiency ROE against Of / S. The results show that intellectual capital is a factor that is very important and significant effect on the quality of the company which in turn directly affects firm value andfinancial performance of the company.